THE EFFECT OF MICROORGANISMS ON FE PRECIPITATION RATES AT NEUTRAL PH - Kasama T.; Murakami T. (My University, 2001)
The effect of microorganisms on Fe precipitation rates at neutral pH in the field was examined. The studied area was a cave having Fe-stalactites composed mainly of ferrihydrite and associated microorganisms. The microorganisms were covered with ferrihydrite. Water associated with stalactites was slightly supersaturated with respect to ferrihydrite, and had a dissolved oxygen concentration of 2 ppm, a pH of 6, and an Fe concentration of approximately 14 ppm. Fe precipitation rates were estimated from decreases in Fe concentrations in water during flowing through the Fe-stalactites. The estimated Fe precipitation rate in the field ranges from 6.8x10-8 to 4.0x10-7 mol/l/s. These values are in good agreement with bulk estimates of Fe-stalactite growth rates derived from the length increase (1.3 cm) of one formation over 30 days. The estimated Fe precipitation rates are faster by about four orders of magnitude than expected inorganic precipitation rates. On-site Fe precipitation experiments with sterilized and unsterilized Fe-stalactites and without Fe-stalactites indicate that microorganisms are the controlling factor accelerating Fe precipitation rates at neutral pH. These results suggest that microbially accelerated Fe precipitation rates are more likely related to exopolysaccharides and microbial surface properties than metabolic precipitation mechanisms.
Keywords: FE-STALACTITES; FERRIHYDRITE; PRECIPITATION